Performance Management of University Financial Budget Execution Relying on Comprehensive Budget Management Strengthening Model - Huwei Li; Yanlin Guo (Advances in Multimedia)
In order to improve the effect of college financial budgeting, this paper combines the comprehensive budget management strengthening model to construct the school financial budget execution performance management model and selects data envelopment analysis (DEA) and stochastic frontier analysis (SFA) as empirical analysis methods. Moreover, this paper puts forward the idea of analyzing the proportion of investment funds and obtains the optimal distribution proportion through mathematical methods. Under the circumstance that the total funding input remains unchanged, this paper adjusts the investment ratio to improve the efficiency of the colleges and centers in the school and combines actual needs to construct an intelligent model of financial budget execution performance management for colleges and universities that relies on the comprehensive budget management enhancement model. In addition, the model effect verification is carried out on this basis. According to the research, the energy system proposed in this paper plays an important role in the performance management evaluation of the financial budget implementation of colleges and universities and can effectively improve the effect of college financial budgets.